2021 TPWRS Best Paper Award - Aristidou, Petros (My University, 2026)
Award for paper: A. Venkatraman, U. Markovic, D. Shchetinin, E. Vrettos, P. Aristidou, and G. Hug, “Improving dynamic performance of low-inertia systems through eigensensitivity optimization,” IEEE Trans. Power Syst., vol. 36, no. 5, pp. 4075–4088, Sep. 2021. The TPWRS editorial board selects the best transaction papers each year for TPWRS Best Paper Awards. The papers are selected from candidate papers that are nominated by the associate editors and published in TPWRS during the past three years.
Keywords: Sciences